2010
DOI: 10.1021/jf903660a
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of Yeast Proteins Extracted into Model Wine during Aging on the Yeast Lees

Abstract: Total protein and protein-associated mannan concentrations were measured, and individual proteins were identified during extraction into model wines over 9 months of aging on the yeast lees following completion of fermentations by seven wine strains of Saccharomyces cerevisiae. In aged wines, protein-associated mannan increased about 6-fold (+/-66%), while total protein only increased 2-fold (+/-20%), which resulted in a significantly greater protein-associated mannan/total protein ratio for three strains. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…As opposed to “wet” chemical analysis, infrared spectroscopic techniques, such as Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFT), have the potential to reveal molecular structures of proteins. These techniques have been implemented to study the protein secondary structure of feeds [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…As opposed to “wet” chemical analysis, infrared spectroscopic techniques, such as Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFT), have the potential to reveal molecular structures of proteins. These techniques have been implemented to study the protein secondary structure of feeds [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…GAPDH is a cell surface protein, 27,28 whereas Cpr1p has been identified in the culture media in Saccharomyces cerevisiae in large-scale secretomic/extraction studies. 29,30 Our results indicated that approximately 33.7-76.7% of these enzymes were secreted in glucose-starved cells. Given that these proteins do not contain typical ER signal sequence, they are secreted via the non-classical pathway.…”
mentioning
confidence: 63%
“…It is reported that Exg1, Bgl2 and Uth1 are anchored to the yeast cell wall by di-sulphide bridges, as they are released from yeast cells upon treatment with reducing agents as DTT [34,35]. During wine fermentations, yeast cells release Exg1 and Bgl2 from the cell wall to the wine [36]. In beer, Fasilo et al (2010) identified Exg1, Bgl2 and Uth1 among the 40 protein fragments, originating from S. cerevisiae [4], and very recently the presence of these three full-length proteins have also been identified in different commercial beers [5].…”
Section: Discussionmentioning
confidence: 99%